Optimizing Employee Performance: Managing Work Stress, Work Environment and Workload - Amalia, Lisa; Wahyuni, Etty Sri; Wibisono, Chablullah (Universitas Batam, 2023)
The main aim of this study was to conduct a thorough investigation into how work stress, work environment, and workload impact employee performance, both individually and in combination. The research focused on 52 employees employed at PT Inline Flow Specialty. Data collection primarily involved administering questionnaires to the participants, and subsequent analysis was conducted using multiple linear regression within a quantitative research framework. Results from the partial t-test revealed that work stress and work environment significantly influenced employee performance, whereas workload did not demonstrate a significant effect. However, when these factors were considered together, they collectively showed a considerable impact on performance. Further examination of the data revealed that the coefficient of determination (R2) indicated that 24.6% of the variation in performance could be explained by work stress, work environment, and workload. However, the bulk of the variation, accounting for 75.4%, was attributed to other unexplored factors. This underscores the intricate nature of performance determinants in the workplace and suggests avenues for future research to delve deeper into these unexplored factors.